Abnormal mitochondrial fusion-fission balance contributes to the progression of experimental sepsis - Gonzalez, Analia Silvia (2014)
Sepsis-associated multiple organ failure is a major cause of mortality characterized by a massive increase of reactive oxygen and nitrogen species (ROS/RNS) and mitochondrial dysfunction. Despite intensive research, determining events in the progression or reversal of the disease are incompletely understood. Herein, we studied two prototype sepsis models: endotoxemia and cecal ligation and puncture (CLP) - which showed very different lethality rates (2.5% and 67%, respectively) - , evaluated iNOS, ROS and respiratory chain activity, and investigated mitochondrial biogenesis and dynamics, as possible processes involved in sepsis outcome. Endotoxemia and CLP showed different iNOS, ROS/RNS, and complex activities time-courses. Moreover, these alterations reverted after 24-h endotoxemia but not after CLP. Mitochondrial biogenesis was not elicited during the first 24 h in either model but instead, 50% mtDNA depletion was observed. Mitochondrial fusion and fission were evaluated using real-time PCR of mitofusin-2 (Mfn2), dynamin-related protein-1 (Drp1), and using electron microscopy. During endotoxemia, we observed a decrease of Mfn2-mRNA levels at 4-6 h, and an increase of mitochondrial fragmentation at 6 h. These parameters reverted at 24 h. In contrast, CLP showed not only decreased Mfn2-mRNA levels at 12-18 h but also increased Drp1-mRNA levels at 4 h, and enhanced and sustained mitochondrial fragmentation. The in vivo pretreatment with mdivi-1 (Drp1 inhibitor) significantly attenuated mitochondrial dysfunction and apoptosis in CLP. Therefore, abnormal fusion-to-fission balance, probably evoked by ROS/RNS secondary to iNOS induction, contributes to the progression of sepsis. Pharmacological targeting of Drp1 may be a potential novel therapeutic tool for sepsis.